Design and optimization of (chemo-)enzymatic processes for the synthesis of hydroxynitriles and their derivatives - Leemans Martin, Laura (2020)
ß-amino alcohols are important building blocks for the synthesis of active pharmaceutical ingredients, where enantiopurity is often crucial. Despite the availability of a range of chiral ß-amino alcohols from a chiral pool, there is a growing demand for new enantioselective synthetic routes to ß-amino alcohols and their derivatives. In this thesis, an asymmetric 2-step chemo-enzymatic cascade that converts 4-anisaldehyde into the ß-amino alcohol derivative (S)-tembamide ((S)-4) has been developed. The first step consists in a concurrent bi-enzymatic synthesis of (S)-4-methoxymandelonitrile benzoate ((S)-3), catalyzed by immobilized Manihot esculenta hydroxynitrile lyase (MeHNL) and Candida antarctica lipase A (CALA). To accomplish this, each biocatalytic reaction was studied separately in search for a window of compatibility and potential cross-interactions between the two reactions were identified. In a second step, the nitrile group is catalytically reduced to give (S)-4, via an acyl transfer of the amino ester formed upon hydrogenation. To achieve hydrogenation of the nitrile moiety with highest chemoselectivity and enantioretention, various parameters such as the catalyst nature and reaction temperature were studied. Finally, after optimization of the chemo-enzymatic cascade, a preparative synthesis of (S)-tembamide was performed. The optimized enzymatic cascade afforded intermediate 3 in 80% yield and 99% e.e. However, due to the low chemoselectivity of the hydrogenation reaction, the total isolated yield of tembamide was 15%, albeit with excellent enantiopurity (98% e.e.). The developed strategy might be transferrable to the synthesis of other N-acyl-ß-amino alcohols with potential biomedical properties. Furthermore, this is the first reported example of a successful combination of an HNL and a lipase in concurrent fashion. Additionally, using site-saturation mutagenesis, it was attempted to improve the cyanolytic activity of halohydrin dehalogenase from Ilumatobacter coccineus YM16-304 (HheG) in order to ...